Melatonin and Other Tryptophan Metabolites Produced by Yeasts: Implications in Cardiovascular and Neurodegenerative Diseases - Hornedo-Ortega, Ruth; Cerezo, Ana B.; Troncoso, Ana M.; Garcia-Parrilla, M. Carmen; Mas, Albert (Frontiers in Microbiology, 2016)
Yeast metabolism produces compounds derived from tryptophan, which are found in fermented beverages, such as wine and beer. Melatonin and serotonin, in particular, may play a significant role due to their bioactivity in humans. Indeed, the former is a neurohormone related to circadiam rhythms, which also has a putative protective effect against degenerative diseases. Serotonin, on the other hand, is a neurotransmitter itself, in addition to being a precursor of melatonin synthesis. This paper summarizes data reported on fermented beverages, to evaluate dietary intake. Additionally, the article reviews observed effects of yeast amino acid metabolites on the prevention of neurodegenerative diseases (Alzheimer’s and Parkinson’s) and angiogenesis, focusing on evidence of the molecular mechanism involved and identification of molecular targets